Wavelet-based auto-counting tool of aedes eggs - Jawahir, W.N.; Yussof, H.W.; Man, M.; Hitam, M.S.; Abdul Hamid, A.A.K.; Awalludin, E.A.; Aezwani, W.; Bakar, W.A. (2018)
Aedes aegypti mosquito species are an important vector of many viruses including dengue and Zika. Preventing or reducing the virus transmission depends entirely on controlling the mosquito vectors. To facilitate a vector control operation, a new image processing tool is developed for counting Aedes eggs so that fecundity estimation can be done automatically replacing the manual counting that requires a lot of efforts and time-consuming. The proposed tool is based on Gabor wavelets to produce a response map that can ease the thresholding process. We test the proposed tool of Aedes eggs counting by comparing with ICount and EggCounter which is freely available on the Internet. The results showed that the proposed method is promising for a reliable estimation of Aedes eggs.